Edukacja dorosłych w laboratorium hydrotroniki napędów robotów mobilnych - Adam Bartnicki; Agnieszka Klimek (Edukacja Ustawiczna Dorosłych)
The continuous development of drive systems of modern machines and devices results in an increase in the demand for qualified engineers in the operation and maintenance of these drives. The article presents a laboratory of hydronics for mobile robots` drives at the Institute of Mechanical Engineering of the Military of Technology and its educational activities for students and engineering staff.